Islamic value sensitive design for psychology clinic information system / Fadzlin Ahmadon - Ahmadon, Fadzlin (2013)
The existing system used by the Hospital Universiti Sains Malaysia (HUSM) Psychology Clinic infringes on several values of both the direct and indirect stakeholders of the system. Most alarmingly, patient’s privacy is violated due to the insufficient control on who can access the patients’ files. Because psychologists are ethically bounded by their profession to put the highest care on safeguarding the privacy of these psychological progress notes, a migration to a more secure system was decided. This new system’s major concern is to make sure the values of the stakeholders are addressed. In order to do this a design methodology that highlights how to embed values into the system itself, Value Sensitive Design (VSD) was chosen. VSD argues that a focus on values needs to be done even before the design stage of the system development. It recommends that direct and indirect stakeholders be identified, the values important to them recognized and reference is made to works in philosophy and ethics in order to define how the values should be managed. This study extracted the definition of values from Islamic traditions of Qur’an and Sunnah and combined it with design suggestions by system design literatures to design and develop a prototype that managed to address the ethical concerns of the stakeholders. From the study, an Islamic Value Sensitive Design (IVSD) model was formed, which is an extension of the existing methodology of Value Sensitive Design. This IVSD model can be beneficial for any future study that wants to address ethical issues from an Islamic perspective. The prototype has shown that the IVSD model can be used to develop a system that embeds Islamic values in its construction which also addresses users’ needs and concerns.